Meningococcal Vaccination in Men Who Have Sex with Men. Issue 2 (5th December 2016) - Blackwell, Christopher W.
Abstract: Recent outbreaks of meningitis in men who have sex with men (MSM) in Los Angeles, Chicago, New York City, and other locations across the United States have heightened public health concerns regarding the increasing incidence of meningococcal infections in this vulnerable population. MSM have unique risk factors that result in greater threat from certain infectious diseases, including meningococcal infection. Men who have sex with men who are infected with HIV are at even higher risk. This article explores the increased risks among MSM in contracting and communicating meningococcal infection, use of vaccination as primary prevention, and outreach strategies that may help address this issue and lessen the disease burden associated with meningococcal infection in these sexual minorities.